Evaluations of wave-induced steady forces and turning motion of a full hull ship in waves - Yasukawa, Hironori; Hirata, Noritaka; Matsumoto, Akinori; Kuroiwa, Ryota; Mizokami, Shuji (Journal of marine science and technology, 2019)
In this paper, we provide new experimental data of the wave-induced steady forces (the added resistance, wave-induced steady lateral force, and yaw moment) acting on a full hull ship in regular waves, and we verify the validity of existing prediction methods for wave-induced steady forces by performing comparisons with results obtained experimentally. For the prediction methods, we consider the zero-speed three-dimensional panel method (3DPM) and the method based on formulas of the wave-induced steady forces that are expressed using the Kochin-function assuming a slender ship (strip theory-based Kochin-function method: SKFM). The results show that the calculation accuracy obtained using 3DPM and SKFM for added resistance and steady lateral force is acceptable for practical purposes although the accuracy is insufficient for the steady yaw moment. In order to confirm the applicability of both methods to the problem of maneuvering in waves, we predict the turning motions of the ship in irregular waves using the calculation results obtained by 3DPM and SKFM for the wave-induced steady forces, and we compare the turning motions with the free-running model test results. Both methods are useful for predicting turning motions in irregular waves.